Identifikasi Senyawa Penyusun Minuman Herbal Serai-Gula Lontar Menggunakan Gas Chromatography-Mass Spectrometry - Putra, I Gede Arie Mahendra; Wrasiati, Luh Putu; Yuarini, Dewa Ayu Anom (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 4 (2022): Jurnal ITEPA, 2023)
This study aims to identify the components in the ethanol extract of the lemongrass-sugar palm herbal drink using the Gas Chromatography- Mass Spectrometry (GC-MS) method. The stages of this research include the extraction process of lemongrass stalk powder using hexane solvent, palm sugar powder using ethanol solvent and lemongrass-sugar palm herbal drink powder using ethanol solvent. Lemongrass-sugar herbal drink powder is a powder with the addition of 10% lemongrass stalks. Furthermore, all of the prepared samples were extracted using the soxhletation method for 5 hours with a ratio of 1:20 (w/v). Extracts from each sample obtained were analyzed with the GC-MS instrument. The compounds identified in the samples of the lemongrass-sugar palm herbal drink powder were 7 compounds such as Methanol (CAS) Carbinol, Ethanol (CAS) Ethyl Alcohol, Pentane, 2-methyl-(CAS) 2-Methylpentane, Pentane, 3-methyl-(CAS) 3- Methylpentane, Hexane (CAS) n-Hexane, Cyclopentane, methyl-(CAS) Methylcyclopentane and Nonadecan,1,2-EPOXI-. These results are almost similar with compounds identified in the sampel of palm sugar powder, except Nonadecan,1,2-EPOXI-, which is thought it come from the lemongrass stalk powder. while in the hexane extract of lemon grass stalk powder, 22 compounds were identified that could be classified as scents component. The conclusion of this study is that palm sugar has a great influence on the components that were thought to be present in the lemongrass-palm sugar herbal drink, which can be seen from the components identified, most of which are components contained in the ethanol extract of palm sugar powder. All the compounds thought to be present in the herbal drink have similarities with the Similarity Index (SI) above 90%.